Laparoscopic‐endoscopic cooperative surgery for early gastric cancer with gastroesophageal varices. Issue 4 (17th February 2020) - Namikawa, Tsutomu; Iwabu, Jun; Munekage, Masaya; Uemura, Sunao; Maeda, Hiromichi; Kitagawa, Hiroyuki; Nakayama, Taku; Fukuhara, Hideo; Inoue, Keiji; Al‐Sheikh, Mariam; Jaiswal, Nalin; Kobayashi, Michiya; et al.
Abstract: This report describes a patient with early gastric cancer with gastroesophageal varices who underwent laparoscopic‐endoscopic cooperative surgery. The patient, a 75‐year‐old woman, was referred to our hospital for the treatment of gastric cancer. Esophagogastroduodenoscopy revealed a superficial spreading‐type tumor on the posterior wall of the upper third of the stomach that was very close to the gastric varices. Biopsy specimens showed a moderately differentiated tubular adenocarcinoma. Abdominal contrast‐enhanced CT showed an enhanced submucosal area with noticeably dilated veins around the perigastric region and no masses in the liver. The patient underwent local resection of the stomach using laparoscopic‐endoscopic cooperative surgery; this procedure was chosen because of the patient's risk of bleeding from the gastric varices in the area adjacent to the cancer during endoscopic submucosal dissection. Macroscopic examination of the resected specimen showed a superficial spreading lesion measuring 55 × 50 mm. The pathological diagnosis was moderately differentiated tubular adenocarcinoma invading the gastric submucosal layer without lymphovascular invasion.